2010
DOI: 10.5194/acp-10-7575-2010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and aerosol characterisation of the troposphere over West Africa during the monsoon period as part of AMMA

Abstract: During June, July and August 2006 five aircraft took part in a campaign over West Africa to observe the aerosol content and chemical composition of the troposphere and lower stratosphere as part of the African Monsoon Multidisciplinary Analysis (AMMA) project. These are the first such measurements in this region during the monsoon period. In addition to providing an overview of the tropospheric composition, this paper provides a description of the measurement strategy (flights performed, instrumental payloads,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 116 publications
3
126
0
Order By: Relevance
“…For example, over Lagos, Nigeria, ozone-enhanced layers are observed in December-February, when burning occurs regionally, and also in July-August, when biomass burning occurs over southern equatorial Africa (Sauvage et al, , 2007b. Such processes have been further investigated in the frame of AMMA (Reeves et al, 2010;Thouret et al, 2009;Mari et al, 2008). Similarly, over Brazzaville, the seasonal cycle of ozone peaks in July-August but a secondary maximum appears in January-February due to transport of ozone and precursors from fires occurring in the Northern Hemisphere (Sauvage et al, , 2007b.…”
Section: Biomass Burningmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, over Lagos, Nigeria, ozone-enhanced layers are observed in December-February, when burning occurs regionally, and also in July-August, when biomass burning occurs over southern equatorial Africa (Sauvage et al, , 2007b. Such processes have been further investigated in the frame of AMMA (Reeves et al, 2010;Thouret et al, 2009;Mari et al, 2008). Similarly, over Brazzaville, the seasonal cycle of ozone peaks in July-August but a secondary maximum appears in January-February due to transport of ozone and precursors from fires occurring in the Northern Hemisphere (Sauvage et al, , 2007b.…”
Section: Biomass Burningmentioning
confidence: 99%
“…Export of polluted air masses is observed throughout the Gulf of Guinea up to the coast of West Africa in the Northern Hemisphere. Reeves et al (2010) provide a clear characterisation of the ozone distribution throughout the troposphere over West Africa during the monsoon period. Owing to previous analysis based on MOZAIC data (Sauvage et al, 2007a and the regular ozone soundings over Cotonou over 2 years (Thouret et al, 2009), it has been shown that the biomass burning seasons in both hemispheres impact the tropospheric ozone profiles in both hemispheres as well.…”
Section: Atmosmentioning
confidence: 99%
“…To provide the quantitative estimate of the mineralogical composition of mineral dust on a regional scale, we report in this paper the synthesis of data from various aircraft and ground-based field campaigns which took place in western Africa in 2006 and 2007. These are the African Monsoon Multidisciplinary Analysis (AMMA) special observing period 0 (SOP0; Rajot et al, 2008), augmented by the airborne Dust and Biomass-burning Experiment (DABEX; Haywood et al, 2008); special observing periods 1 and 2 (SOP1-2; Reeves et al, 2010); the Dust Outflow and Deposition to the Ocean (DODO; McConnell et al, 2008) and the Geostationary Earth Radiation Budget Intercomparison of Longwave…”
Section: P Formenti Et Al: Mapping the Physico-chemical Properties mentioning
confidence: 99%
“…The aircraft performed 13 research flights in the area between 8 and 18 • N, including three dedicated excursion to the north of Niger, toward the Aïr Mountains and the Ténéré desert, to probe specifically mineral dust which was being transported. In summertime, the observations were conducted onboard the Service des Avions Français Instruments pour la Recherche en Environnement (SAFIRE) ATR-42, which operated 20 research flights in the area between 6 and 20 • N, thus crossing the ITCZ to the north; this was done in order to contrast the Sahara and the Sahelian dust properties in their respective boundary layers (Reeves et al, 2010;Formenti et al, 2011b).…”
Section: Field Campaignsmentioning
confidence: 99%
“…Considering that OMI data integrate the atmospheric column of HCHO, comparison with aircraft observations are of particular interest. The airborne HCHO measurements made during INTEX-B (Intercontinental Chemical Transport Experiment B) (Singh et al, 2009;Fried et al, 2011) Multidisciplinary Analysis) (Reeves et al, 2010;Borbon et al, 2012) . We compute the ratio of the posterior to the prior bias between modeled and observed concentrations.…”
Section: Evaluation With Independent Datamentioning
confidence: 99%